Thermal activation of palygorskite for enhanced fluoride removal under alkaline conditions. (December 2022) - Mo, Xinxin; Zhuang, Ziyi; Ren, Chao; Li, Wei
Abstract: Fluoride contamination of groundwater is a global environmental problem. Based on adsorption treatment strategies, magnesium-based materials have shown potential for defluoridation of this water source. In this research, we calcined raw palygorskite (RPAL), a natural magnesium-rich clay, at different temperatures (100–1000 °C), to examine the defluoridation performance. The evolution of the morphology, physical-chemical properties, and crystal structure was characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), and 27 Al and 29 Si solid-state nuclear magnetic resonance (NMR) spectroscopy. Palygorskite calcined at 200 °C (CP200) had F − uptake of ∼1.6 mg F − /g within a neutral-to-basic pH region of F-contaminated groundwater (e.g., pH 7–9), which is 5–6 times larger than that for RPAL. Additionally, CP200 and CP400 exhibited comparatively greater adsorption performance for fluoride removal compared with activated alumina (AA) under alkaline conditions (e.g., 1.5–3 times at pH ≥ 9). The dependence of fluoride uptake by the calcined samples appeared to be related to major changes in the crystal structure of palygorskite, particularly the dehydration of zeolite waters and partially coordinated water within pores. The exposed > MgOH2 groups at tunnel edges may play an important role in fluoride removal, especially at elevated pH. The higher stability under alkaline conditions and the lower sensitivity to pH compared with AA demonstrated the potential of calcined palygorskite as an effective magnesium-based clay for the remediation of fluoride contamination of groundwater. Highlights: Structural and physical-chemical properties of palygorskite during calcination were extensively characterized. Palygorskites calcined at 200–400 °C exhibited the optimum defluoridation performance. Fluoride removal under alkaline conditions was enhanced more than 5 times after calcination. The exposed > MgOH2 sites at tunnel edges may play an important role. Thermally activated palygorskite may be used as an effective natural Mg-based adsorbent for fluoride contaminated groundwater.